Impact Of Cognitive Impairment on The Quality Of Life In Older Patients Hastened By Hypertensive Encephalopathy (Eurasian Medical Research Periodical, 2024)
Vascular diseases of the brain remain one of the most acute medical and social problems causing enormous economic damage to society. Among them, cerebral stroke occupies a special place due to the high mortality rate, significant disability and social maladaptation of patients. Stroke doubles the risk of dementia in the elderly. Arterial hypertension (AH) is the most common disease of the cardiovascular system, which affects about 40% of the adult population in Uzbekistan. In older age groups, the frequency of its occurrence reaches 80%. The disease affects all organs, but the kidneys and brain are most susceptible to pathological changes. Brain damage is caused by tortuosity or stenosis of the carotid arteries, thickening of the intima-media complex, endothelial dysfunction, etc. One of the most common disorders is a lesion of the white matter of the brain — hypertensive encephalopathy (GE)